Analisis Dampak Perdagangan Internasional Komoditas Crude Palm Oil (CPO) Terhadap Pertumbuhan Ekonomi di Indonesia - Purnama, Lili; Haryono, Slamet; Hidayat, Faisal (Jurnal Magister Ekonomi Syariah, 2023)
Indonesia is a country that adheres to an open economic system with international trade as a driving force for economic growth. This study aims to analyze the impact of international trade on Crude Palm Oil (CPO) commodities, which consist of CPO exports, CPO production, exchange rates, inflation, and unemployment, on economic growth in Indonesia. The method used is multiple linear regression using the Ordinary Least Square (OLS) approach and the eviews 10 application. The data used is an annual time series from 1990–2021. The results of the study simultaneously show that the variables of CPO exports, CPO production, exchange rates, inflation, and unemployment have a joint effect on economic growth. While partially CPO exports have a significant positive effect on economic growth, CPO production, exchange rates and inflation have a negative and insignificant relationship to economic growth and unemployment has a significant negative effect on economic growth in Indonesia.